Physically cross-linked PVA/f-MWCNTs nanocomposite hydrogel with enhanced thermal, mechanical, and dielectric properties - Sharma S.; Bhende M.; Verma H.R.; Kumar S. (My University, 2025)
This work offers a new method for the preparation of poly (vinyl alcohol)/f-MWCNTs nanocomposite hydrogel. Employing a physical cross-linking method, fabricated high-strength nanocomposite hydrogel in one step at room temperature without following the traditional repeated freeze-thaw method. Optical microscopy images indicate the uniform dispersion of f-MWCNTs in the PVA matrix with average agglomerate size of 5–6 µm. Morphology investigation showed entangled, more dense network structure after addition of f-MWCNTs. Scissoring of inter chain H-bonding and establishing of intermolecular H-bonding between -OH and -COOH group of PVA and f-MWCNTs examined by ATR-FTIR. Delay in thermal degradation of PVA/f-MWCNTs nanocomposite hydrogel with f-MWCNTs suggested by thermos-gravimetry analysis. Improved melting and crystalline temperature examined by differential scanning calorimetry. PVA/f-MWCNTs nanocomposite hydrogel showed ⁓ 5 and 6 times of modulus and hardness respectively than pristine PVA hydrogel. Oscillatory rheology analysis suggests the robust gel-like network formed upon addition of f-MWCNTs into the PVA matrix. PVA/f-MWCNTs nanocomposite hydrogel showed 13 times dielectric constant than pristine PVA hydrogel along with small dielectric loss investigated by broadband dielectric spectroscopy (BDS). Enhanced thermal, mechanical and dielectric properties make the fabricated PVA/f-MWCNTs nanocomposite hydrogel a potential candidate for the energy storage device and electronics application. © 2024 Elsevier Ltd